Estratégia Saúde da Família no Município de Belém-PA: o território e a complexidade do processo saúde-doença no bairro da Terra Firme - REZEGUE, Danilo Magalhães (Universidade Federal do Pará, 2024)
In the field of Collective Health, the debate about the interrelations between territory and health has as one of its communicating vessels the Family Health Strategy, a public policy based on the principles of Primary Health Care, whose organization of the work process follows a territorial and multiprofessional logic with the perspective of bringing the services of individuals, families, communities and social groups closer together. Following the theoretical guidelines of the social production of space and critical epidemiology, this research adopts the territory as a category of privileged analysis for the understanding of the factors related to the social determination of the health-disease process, adopting as locus the neighborhood of Terra Firme in Belém - PA, a pioneer neighborhood during the process of implementing the Family Health Strategy in the municipality. Taking as a methodological perspective the clues of post-structuralist orientation cartography, after a period of immersion in the territory, the research process comprised the registration of 12 open and semi-structured interviews with social agents who lived or lived the historical context of the neighborhood from different points of view such as residents, doctor, former manager, afro-religious leadership and popular leaderships. It was observed that the understanding of the healthdisease process from the territorial approach requires theoretical and methodological efforts that allow us to understand the dynamics surrounding territory and health beyond a strictly functionalist perspective, administrative and bureaucratic and superficially operational. It is a question of understanding the territory based on its relational aspects, its symbologies and uses, as well as understanding it as a dimension of practices and knowledge that can re-signify health policies and the dynamics of the organization of services from a local perspective.